Thermoregulation in young athletes exercising in hot environments - Bass, S.; Inge, K. (International SportMed Journal, 2001)
Children are less efficient thermoregulators than are adults. During exercise, sweat evaporation is the most important physiological means of cooling the body. The sweat response in children, however, is less efficient than in adults, so children dissipate less heat though evaporative sweating and more through convection (the loss of heat through the skin) plus radiation. Children and adolescents with high levels of body fat and heavy builds are more susceptible to heat stress because they dissipate body heat less efficiently. Maintaining adequate hydration is crucial for preventing heat stress. Although water is often described as the best choice of fluid, studies on voluntary drinking habits and flavor preferences in children and adolescents suggest that greater consumption occurs when sports drinks are offered instead of water. Although a child`s sweat contains less sodium and chloride than an adult`s does, there appears to be no evidence that a child`s performance improves when given beverages more diluted than those currently recommended for adults. More information is necessary to identify the optimal electrolyte and carbohydrate content of sports drinks for young athletes.